(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Fighting terrorism is one of the challenging aspects for civilization. Having ability to foresee the future threats can make the lives of humans more easy and safe. Terrorism has always been biggest challenge and we have always fight back it back united. Since the future is all about AI and technology has been advancing day by day, it’s very necessary that we also unite with AI and IoT to fight the terrorism together.